Bayesian Evaluation of Pentaspline Pulsed Field Ablation Compared to High‐Power Radiofrequency Ablation in Atrial Fibrillation...Mariani MV, Matteucci A, Pierucci N, et al. Pentaspline Pulsed Field Ablation Versus High‐Power Short‐Duration/Very High‐Power Short‐Duration Radiofrequency Ablation in Atrial Fibrillation: A Meta‐Analysis. Journal of Cardiovascular Electrophysiology (J CARDIOVASC ELECTROPHYSIOL), 2025; 36(9): 2165-2178. - Barbosa, Lucas M.; Oliveira, Vinícius Martins Rodrigues; Guedes, Lara; Nunes, Maria do Carmo P. (Journal of Cardiovascular Electrophysiology, 2025)
The article focuses on a meta-analysis examining whether pulsed field ablation (PFA) reduces the risk of atrial fibrillation recurrence compared to high-power short-duration (HPSD) or very HPSD radiofrequency ablation. The study indicates that PFA is significantly associated with a lower recurrence risk, although the frequentist framework used may limit the reliability of these findings. A Bayesian approach was employed to provide more intuitive results, revealing an average odds ratio of 0.63, with a 99% probability that the true odds ratio is less than 1. The authors suggest that further research, such as an individual patient meta-analysis or a large-scale controlled trial, could provide more definitive conclusions.